2018
DOI: 10.1007/978-3-319-90143-5_10
|View full text |Cite
|
Sign up to set email alerts
|

New Frontiers of Metallomics: Elemental and Species-Specific Analysis and Imaging of Single Cells

Abstract: Single cells represent the basic building units of life, and thus their study is one the most important areas of research. However, classical analysis of biological cells eludes the investigation of cell-to-cell differences to obtain information about the intracellular distribution since it only provides information by averaging over a huge number of cells. For this reason, chemical analysis of single cells is an expanding area of research nowadays. In this context, metallomics research is going down to the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 78 publications
(91 reference statements)
0
4
0
1
Order By: Relevance
“…This Feature provides just a few select examples for such developments in bioanalytical NMR, MS, and optical spectroscopy that have enabled the characterization of transcripts, proteins, peptides, metabolites, and elements in single cells in important models of basic biological and translational investigations. Among other developments, we would like to point to single-cell metallomics, the studies that determine the trace metals and the metal complexes within a cell that are critically important in biological processes including metabolic signaling (see, e.g., refs and and energy-dispersive X-ray analysis-electron microscopy (EDX-EM)), which allows interpretation of macromolecular functionality by analyzing endogenous elements, labels (gold and cadmium-based nanoparticles), as well as stains at nanometer resolution . Other recent developments include NanoString gene expression profiling, which provides a highly sensitive alternative to scRNA-seq for quantitative transcriptional profiling for a predefined set of genes of interest, , and cryoelectron microscopy (cryoEM), which has the potential to uncover the dynamics of macromolecular machines at the single-cell level. , The data resulting from the above-mentioned studies have already begun to uncover previously unavailable molecular information on cell-to-cell differences during states of health and disease, which in turn can now be used to design hypothesis-driven studies to test for the functional significance of the observed molecular differences between cells.…”
Section: Discussionmentioning
confidence: 99%
“…This Feature provides just a few select examples for such developments in bioanalytical NMR, MS, and optical spectroscopy that have enabled the characterization of transcripts, proteins, peptides, metabolites, and elements in single cells in important models of basic biological and translational investigations. Among other developments, we would like to point to single-cell metallomics, the studies that determine the trace metals and the metal complexes within a cell that are critically important in biological processes including metabolic signaling (see, e.g., refs and and energy-dispersive X-ray analysis-electron microscopy (EDX-EM)), which allows interpretation of macromolecular functionality by analyzing endogenous elements, labels (gold and cadmium-based nanoparticles), as well as stains at nanometer resolution . Other recent developments include NanoString gene expression profiling, which provides a highly sensitive alternative to scRNA-seq for quantitative transcriptional profiling for a predefined set of genes of interest, , and cryoelectron microscopy (cryoEM), which has the potential to uncover the dynamics of macromolecular machines at the single-cell level. , The data resulting from the above-mentioned studies have already begun to uncover previously unavailable molecular information on cell-to-cell differences during states of health and disease, which in turn can now be used to design hypothesis-driven studies to test for the functional significance of the observed molecular differences between cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the inherent nature of mass-spectrometry applications, which rely on the removal of material for elemental analysis, makes it difficult, but not impossible, to analyze whole cells quantitatively, requiring subsequent, repeated scans of the same area to fully capture the three-dimensional cell. 236 …”
Section: Elemental Composition Of Cellsmentioning
confidence: 99%
“…The prominent advantage for quantitative mapping is demonstrated by its detection limits at the microgram per gram and nanogram per gram concentration ranges (Sabine Becker, 2013). Thus, it is attractive in the mapping of metals, metalloids and nonmetals, isotopes, and metallodrugs in organs at the trace and ultra‐trace level (Chavatte et al, 2020; Doble et al, 2021; Hare et al, 2014; Lee et al, 2017; Theiner et al, 2019), and it also has been extended for the 3D elemental distribution profile in single cells with the increased interest and advances in image resolution (Jiménez‐Lamana et al, 2018; Y. Meng et al, 2021; Westerhausen et al, 2019).…”
Section: Different Types Of Msi Principles and Techniquesmentioning
confidence: 99%